Antibodies to m‐type phospholipase A2 receptor in children with idiopathic membranous nephropathy. (August 2015) - Kumar, Vinod; Ramachandran, Raja; Kumar, Ashwani; Nada, Ritambhra; Suri, Deepti; Gupta, Anju; Kohli, Harbir Singh; Gupta, Krishan Lal; Jha, Vivekanand
Abstract: Idiopathic membranous nephropathy (IMN), the commonest cause of adult nephrotic syndrome (NS), accounts for only a minority of paediatric NS. Antibodies to m‐type phospholipase A2 receptor (PLA2R) are seen in two‐thirds of adult IMN cases. PLA2R staining in glomerular deposits is observed in 74% and 45% of adult and paediatric IMN cases, respectively. However, there are no reports of anti‐PLA2R in paediatric IMN. We evaluated anti‐PLA2R levels and PLA2R in gloemrular deposits in paediatric IMN seen at our center. Five cases were enrolled, all the cases stained for PLA2R in glomeruli and three (60%) had antibodies to PLA2R antigen. There was a parellel reduction in proteinuria and anti‐PLA2R titer. The present report suggests that PLA2R has a contributory role in the pathogenesis of paediatric IMN.